2019
DOI: 10.1124/jpet.118.255893
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Jing-Fang Powder n-Butanol Extract and Its Isolated Fraction D on Lipopolysaccharide-Induced Inflammation in RAW264.7 Cells

Abstract: The Jing-Fang powder n-butanol extract (JFNE) has antiinflammatory properties; however, its active ingredient remains unknown. In addition, the mechanism by which JFNE exerts its anti-inflammatory effects on lipopolysaccharide (LPS)-induced inflammation in RAW264.7 cells is yet to be explored. In this study, JFNE was isolated by chromatography to obtain fraction D. We found that pretreatment of LPS-induced RAW264.7 cells with JFNE and fraction D for 3 hours significantly reduced the levels of nitric oxide (NO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…An interesting factor is that at the end of the last century, it was shown that the treatment of glia and cultured smooth muscle cells of the rat colon with IL-1β led to a significant increase in the activity of inducible nitric oxide synthase (iNOS) [ 270 ]. Similarly to the above, it was found that a decrease in IL-1β and IL-6 levels, as well as the suppression of mRNA expression of genes encoding these cytokines, correlated with the lower NO release levels in RAW264.7 cells inflammation model under the action of anti-inflammatory fraction A [ 300 ]. IL-6 was also known to be activated by prostaglandin E2 (PGE2) that is formed during the reaction catalyzed by cyclooxygenase-2 [ 301 ], in which the elevated levels are observed in inflammatory macrophages in various types of cancer [ 75 , 302 , 303 , 304 ].…”
Section: Role Of Inflammation In Cancer Progressionmentioning
confidence: 76%
“…An interesting factor is that at the end of the last century, it was shown that the treatment of glia and cultured smooth muscle cells of the rat colon with IL-1β led to a significant increase in the activity of inducible nitric oxide synthase (iNOS) [ 270 ]. Similarly to the above, it was found that a decrease in IL-1β and IL-6 levels, as well as the suppression of mRNA expression of genes encoding these cytokines, correlated with the lower NO release levels in RAW264.7 cells inflammation model under the action of anti-inflammatory fraction A [ 300 ]. IL-6 was also known to be activated by prostaglandin E2 (PGE2) that is formed during the reaction catalyzed by cyclooxygenase-2 [ 301 ], in which the elevated levels are observed in inflammatory macrophages in various types of cancer [ 75 , 302 , 303 , 304 ].…”
Section: Role Of Inflammation In Cancer Progressionmentioning
confidence: 76%
“…Our sample sizes have remained relatively small, necessitating further exploration with larger cohorts to draw more robust conclusions. Moreover, the specific roles and contributions of CXCL5 and CXCL8 in the observed fold changes require a comprehensive investigation 30 …”
Section: Discussionmentioning
confidence: 99%
“…Jingfangsan is composed of a 1:1 combination of Schizonepetae Herba (Jingjie) and Saposhnikoviae Radix (Fangfeng), whose active ingredient in an N-butanol extract exerts anti-inflammatory and anti-allergic effects. 113,114 JFNE-A is a bioactive ingredient fractionated from this compound. According to a previous study, 115 JFNE-A treatment significantly alleviates LPS-induced pathological changes in the lungs of ALI mice.…”
Section: N-butanol Extract Of Jingfangsanmentioning
confidence: 99%